Construction and characteristics of a novel green photocatalyst:iron (III) doped titania nanomesh. Issue 16 (15th August 2021) - Lu, Yuan; Huang, Bingxuan; Xu, Xiaoling; Liu, Yansheng; Cheng, Andi; Hou, Junwei
Abstract: In this work, a green Fe-doped TiO2 photocatalyst was successfully synthesized on Ti mesh through the chemical impregnation and anodization method. The influence of sample Fe-content on the photocatalytic performance was investigated in detail. Ordered TiO2 nanomesh was compactly decorated with nanospheres to form a novel photocatalyst Fe-doped TiO2 with anatase phase. Simultaneously, it exhibits higher light absorption intensity compared to the pristine TiO2 within the visible light range, and its absorption peak has a redshift. The VSM results showed that the sample has excellent magnetic properties. It is hard to achieve magnetic agglomeration after magnetic field removal, which benefits the strong recyclability and reusability of Fe-doped TiO2 photocatalyst. Importantly, this higher visible-light photoresponse of TiO2 was clearly obtained after Fe doping. When the Fe-content was 0.6 wt%, the degradation rate of methylene blue reached 87.9% under simulated sunlight irradiation for 2.5 h. The prepared nanocrystalline photocatalyst demonstrated excellent photocatalysis because of its prominent crystal morphology, strengthen light-absorption capacity, and commendable inhibition recombination of photo-induced electron-hole.